On the human capital of Inca Indios before and after the Spanish conquest: Was there a "pre-colonial legacy"? - Dácil-Tania Juif; Joerg Baten (University of Tübingen, Faculty of Economics and Social Sciences, 2012)
Not only the colonial period, but also the pre-colonial times might have influenced later development patterns. In this study we assess a potential pre-colonial legacy hypothesis for the case of the Andean region. In order to analyze the hypothesis, we study the human capital of Inca Indios, using age-heaping-based techniques to estimate basic numeracy skills. We find that Peruvian Inca Indios had only around half the numeracy level of the Spanish invaders. The hypothesis holds even after adjusting for a number of potential biases. Moreover, the finding has also crucial implications for the narrative of the military crisis of the Inca Empire. A number of explanations have been given as to why the Old American Empires were not able to defend their territory against the Spanish invaders in the early 16th century. We add an economic hypothesis to the debate and test it with new evidence: Were the human capital formation efforts of the Inca economy perhaps too limited, making it difficult to react appropriately to the Spanish challenge?
urn:nbn:de:bsz:21-opus-60289
Keywords: I25; N30; N36; O15; 330; human capital; age-heaping; Inca empire; inequality; growth